2019
DOI: 10.1002/ase.1887
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Student Perceptions of a Dissection‐Based Undergraduate Gross Anatomy Course Using Q Methodology

Abstract: The demand for upper‐level undergraduate dissection‐based anatomy courses is growing, as professional programs require more advanced anatomy training prior to matriculation. To address this need, Indiana University School of Medicine (IUSM) partnered with Indiana University‐Purdue University Indianapolis—a large, urban, life science‐focused campus nearby to IUSM—to offer an undergraduate, dissection‐based course in regional gross anatomy. Because this is a new course, a deeper post‐course evaluation of student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
(44 reference statements)
0
8
0
Order By: Relevance
“…The majority of visiting students also reported the laboratory tour experience either maintained or increased their existing interest in pursuing a healthcare career. Studies have demonstrated that engaging with cadaver dissection, prosections, and isolated organs can increase students' interest in health professions careers (Zayas & McGuigan, 2006; Achilly, 2017; Byram et al, 2020). Students expressed awe at the first‐hand experience of anatomy and pathology, which could serve as a defining moment that sparks a life‐long fascination with the health sciences.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of visiting students also reported the laboratory tour experience either maintained or increased their existing interest in pursuing a healthcare career. Studies have demonstrated that engaging with cadaver dissection, prosections, and isolated organs can increase students' interest in health professions careers (Zayas & McGuigan, 2006; Achilly, 2017; Byram et al, 2020). Students expressed awe at the first‐hand experience of anatomy and pathology, which could serve as a defining moment that sparks a life‐long fascination with the health sciences.…”
Section: Discussionmentioning
confidence: 99%
“…Q-methodology has been shown to be a useful approach to end-of-term course evaluations for examining students’ perceptions regarding course content and delivery 11 , 12 , 28 . Although literature is scarce in the use of this robust approach for evaluating change over time, our results demonstrate that Q-methodology can also reveal clear granular findings on changes in perceptions over time related to course evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…This study took place in the context of the Cadaveric Human Anatomy (BIOL N461) course at Indiana University—Purdue University Indianapolis (IUPUI), an advanced‐level undergraduate course for students interested in health professional programs (e.g., physical therapy, physician assistant, medicine, etc.). More details about the overall course structure can be found in Byram and colleagues (2020). The FPP was first implemented in the spring semester of 2020 as the course instructors sought to formalize what was an informal, or even implicit, focus on humanism in the course.…”
Section: Methodsmentioning
confidence: 99%